Literature Review: Risk Factors Affecting The Incidence Of Soil-Transmitted Helminths (Sth) Infection In Adults - Rachmawati, Farras Arlinda; Radi, Radi; Rejeki, Dwi Sarwani Sri; Wijayanti, Siwi Pramatama Mars; Wijayanti, Mars (Jurnal Riset Kesehatan, 2025)
Background: Soil-transmitted helminths (STH) infection is still a problem in many countries. Studies on risk factors for soil-transmitted helminths (STH) infection are still more focused on children, while studies in adults are limited. This study aims to summarize risk factors for soil-transmitted helminths (STH) infection in adults. Method: This study used a literature review method by collecting journals from Google Scholar, PubMed, and ScienceDirect. Data was collected using the keywords risk factor, soil-transmitted helmet, and adult.Â  The article to be reviewed is a research conducted in 2019 - 2023. Result: The results of the article search were obtained as many as 861 articles which were then selected using inclusion and exclusion criteria so that as many as 10 articles were received for review. The results of the review of the entire article found that the risk factors for soil-transmitted helminths (STH) infection in adults are individual factors (Education level, gender, age, and type of occupation ), socioeconomic (Community ethnicity, area of residence, and population density), and Personal hygiene (habit of washing food before consumption, nail hygiene, interaction with animals, waste or dirt removal, handwashing habit, soil-eating habit, and boiling drinking water)). Conclusion: Risk factors for soil-transmitted helminths (STH) are individual, socioeconomic, and personal hygiene